Lingvocultural Studies Schools And Lingvocultural Research In Uzbek Linguistics (Journal of Pedagogical Inventions and Practices, 2024)
This article examines the development of linguocultural studies within the framework of the anthropocentric paradigm, emphasizing its application in Uzbek linguistics. The anthropocentric paradigm views language as an open system deeply intertwined with society, culture, and human psychology. While globally recognized disciplines such as sociolinguistics, ethnolinguistics, and cognitive linguistics have extensively explored these interconnections, their implementation in uzbek linguistics remains underdeveloped.